Kritik Pemikiran Arab: Metode Dekonstruksi Mohammed Arkoun - Soekarba, Siti Rohmah (Wacana, Journal of the Humanities of Indonesia, 2006)
Mohammed Arkoun is one of an international Islamic modern thinker that his thought comes into Islamic thinking discourses in Indonesia recently. His Islamic thought were influenced by the modern philosophy concepts such as "myths" of Paul Ricouer, postmodern concepts like 'discourse' and 'episteme', which were developed by Michel Foucault as well as 'deconstruction' of Jacques Derrida. If Derrida focused on deconstruction of a discourse as a final concept, on the other hand Arkoun insisted that 'deconstruction' must be followed by 'reconstruction'. Arkoun's reconstruction leaves the limitation, the rigidity and deviation from the past. Arkoun proposes two ways: firstly it is 'ijtih d' and subsequently it is Islamic critical reason with the whole of critical meaning. In this research the method I used was library investigation. Based on the result I came into the conclusion that Arkoun loss the communication with the scholars in the Islamic world, particularly in the Middle East tradition. Since then, he applied the method of deconstruction that Islamic world percept it was going too far.